Right to Information Act and Employee Relations in India - Singh, Shalini (Prabandhan: Indian Journal of Management, 2012)
There has been a tremendous growth in information and technology in the 21st century, which primarily aims to equip people to make informed and better decisions. The Right to Information Act, passed by the Indian Parliament in the year 2005 has proven to be a landmark for good governance and has a far-reaching impact in having better and informed employee relations and achieve greater transparency and accountability in the working of organizations. It is believed that the RTI Act is limited to government and public authorities, and does not apply to the private sector. The purpose of this paper is to study the applicability of the Right to Information Act on the Public and Private Sector organizations and its relevance for the employees of both the private sector and public authorities and how this tool can be used for the betterment of employee relations in organizations.